2017
DOI: 10.1038/s41598-017-14809-8
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric BMP4 signalling improves the realism of kidney organoids

Abstract: We present a strategy for increasing the anatomical realism of organoids by applying asymmetric cues to mimic spatial information that is present in natural embryonic development, and demonstrate it using mouse kidney organoids. Existing methods for making kidney organoids in mice yield developing nephrons arranged around a symmetrical collecting duct tree that has no ureter. We use transplant experiments to demonstrate plasticity in the fate choice between collecting duct and ureter, and show that an environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…For instance, BMP4 is essential for mesoderm formation and patterning [46, 47]. Recently, BMP4 was shown to contribute to branching of the collecting duct in kidney organoid formation [48]. In accordance with this pathway activation in EL clones that maintain both epithelial phenotype and epithelial transcriptional signature, several BMP proteins (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, BMP4 is essential for mesoderm formation and patterning [46, 47]. Recently, BMP4 was shown to contribute to branching of the collecting duct in kidney organoid formation [48]. In accordance with this pathway activation in EL clones that maintain both epithelial phenotype and epithelial transcriptional signature, several BMP proteins (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, several research groups are studying the molecular cues that direct the development of the ureter and urinary bladder. For example bone morphogenetic protein 4-soaked beads placed near an organoid broke the symmetry of the system, causing a nearby collecting duct to develop into an ureter-like 'trunk', while away from the bead collecting duct branching and nephron formation were not disturbed [100]. On a side note, considerable variations between experiments, clones, as well as research groups, have been reported, which could partly be related to the several protocols currently used to obtain kidney organoids [101].…”
Section: Kidney Organoidsmentioning
confidence: 99%
“…Moreover, this system has been applied to construct UB-like tubules from healthy individuals and a patient with a PAX2 mutation and to study normal UB developmental processes and patient-specific defects. A different approach has shown that the local application of signals (e.g., bead-releasing morphogenetic factors) ( Mills et al, 2017 ) or technical manipulations of engineered tissues (e.g., assembly of previously engineered organ component tissues) ( Taguchi and Nishinakamura, 2017 ) could be used to add key missing information to self-organizing tissue to produce more anatomically realistic organoids.…”
Section: Key Technical Milestones To Be Achievedmentioning
confidence: 99%